KONSERVASI DAN PARIWISATA: STUDY KASUS PENGELOLAAN GREEN CANYON PANGANDARAN - Muhammad Ilham Rahimullah; Siti Fadjarajani; Cahya Darmawan (Universitas Nusa Cendana, 2025)
Green Canyon Pangandaran is a renowned natural tourism destination known for its stunning ecosystem. However, this breathtaking natural attraction also faces challenges in maintaining a balance between environmental conservation and tourism growth. This study aims to understand the conservation strategies implemented in Green Canyon and their impact on both the ecosystem and the tourism industry in the area. This research employs a qualitative approach using observation, interviews, and literature studies. The findings indicate that implementing a community-based ecotourism concept, enforcing strict regulations on tourism activities, and providing environmental education for visitors and tourism stakeholders play a crucial role in maintaining a balance between nature conservation and economic benefits. However, challenges remain, such as the surge in tourist numbers without adequate supervision and the lack of environmental awareness among some visitors. To ensure the sustainability of Green Canyon, close collaboration between the government, local communities, and tourism operators is essential in implementing more sustainable policies. This study provides recommendations for conservation-based management strategies to ensure that Green Canyon and other natural tourism destinations can continue to be enjoyed by future generations without compromising environmental preservation.